Kontribusi Mahasiswa dalam Pengelolaan Website Desa Sebagai Media Komunikasi Pariwisata - Mulyani, Henny Sri; Basith, Achmad Abdul; Kusmayadi, Ika Merdekawati; Sirait, Rinda Aunilah; Gumilar, Gumgum; Sjafirah, Nuryah Asri (Lembaga penelitian dan pengabdian kepada masyrakat, 2024)
A team of students of the Community Service Program, in collaboration with its lecturers, carried out Community Service in Cipicung Village, Jatigede District, Sumedang Regency, with the theme of journalistic content management and website development training for tourist areas. This Community Service aims to improve the ability of website managers to promote Jatigede's tourism potential more effectively, equip managers with journalistic content creation skills to have attractive information and encourage the community to participate and become the main actors in sustainably promoting Jatigede tourist destinations. The implementation method was carried out through lectures, discussions, practices and simulations. These collaborative community service activities produced four articles contents and four videos contents uploaded to the Jatigede District website and YouTube with the theme of potential, superior products, the benefits of mango “gedong gincu”, Small and Medium Enterprise (SME) products and the tourism potential of Al-Kamil Mosque. In addition, the training results also showed an increase in the knowledge and ability of village and sub-district website managers in Jatigede. This activity also received a positive and sustainable response as a fostered area.